2022
DOI: 10.1111/jfd.13715
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous polyunsaturated fatty acids (PUFAs) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A‐layer strain of Aeromonas salmonicida

Abstract: Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Interestingly, Hofer et al showed that polyunsaturated fatty acids (PUFAs) could generate modest protection or vulnerability to polymyxin B and colistin in Aeromonas salmonicida. They concluded that diverse, strain-specific responses to exogenous PUFAs may be an adaptive survival strategy in bacteria that fluctuate between fish and environmental niches [48]. Finally, Bordetella pertussis polysaccharide (Bps) was shown to resist AMP (LL-37, polymyxin B, HNP-1, and HNP-2) killing, helping 'shield' non-pathogenic K12 E. coli and increase in vivo bacterial survival in the respiratory tract [49].…”
Section: Amp Resistancementioning
confidence: 99%
“…Interestingly, Hofer et al showed that polyunsaturated fatty acids (PUFAs) could generate modest protection or vulnerability to polymyxin B and colistin in Aeromonas salmonicida. They concluded that diverse, strain-specific responses to exogenous PUFAs may be an adaptive survival strategy in bacteria that fluctuate between fish and environmental niches [48]. Finally, Bordetella pertussis polysaccharide (Bps) was shown to resist AMP (LL-37, polymyxin B, HNP-1, and HNP-2) killing, helping 'shield' non-pathogenic K12 E. coli and increase in vivo bacterial survival in the respiratory tract [49].…”
Section: Amp Resistancementioning
confidence: 99%
“…Gammaproteobacteria contains many pathogens, such as several Vibrio species ( cholerae , parahaemolyticus , vulnificus , and alginolyticus) , Allivibrio ficheri , Klebsiella pneumoniae , and Pseudomonas aeruginosa , and the model bacterial organism Escherichia coli [ [3] , [4] , [5] , [6] , [7] , [8] ]. Many members of this class, including all the aforementioned species, are able to incorporate exogenous fatty acids, including polyunsaturated fatty acids (PUFAs), into the phospholipids of their membranes [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Such assimilation results in phospholipid structural modifications, causing increased membrane permeability to hydrophobic compounds and altered resistance to certain antibiotics.…”
Section: Introductionmentioning
confidence: 99%